Programa científico para o monitoramento em tempo real ou pós-processado das irregularidades ionosféricas e cintilação dos sinais GNSS - Pereira, Vinícius Amadeu Stuani [UNESP]; Camargo, Paulo De Oliveira [UNESP] (FapUNIFESP (SciELO), 2016)
Brazil is one of the countries that suffer more the effects of the ionosphere, especially those from the Equatorial Ionization Anomaly, ionospheric irregularities and scintillation of GNSS (Global Navigation Satellite System) signals. Several strategies can be used to minimize the effects, such as: ionospheric models, IONEX files or ion-free linear combination. In the case of monitoring of the ionosphere the situation is different. The amount of instruments dedicated to the study of ionospheric layer is reduced in the Brazilian region. In this context it developed a scientific program, namely Ion_Index, in order to estimate indicators of levels of ionospheric irregularities and scintillation of GNSS signals in real time or post-processed using the existing infrastructure of GNSS data public active networks, as the RBMC, GNSS-SP and CALIBRA, thus transforming GNSS stations in monitoring stations of the ionospheric layer. This way it is provided an increase in the spatial resolution of the information on the ionosphere behavior in the Brazilian region, allowing a better understanding and contributing to the development or enhancement of mitigation models. Experiments using digital ionosondes and PolaRxS-PRO Septentrio receivers data (external sources) prove the efficiency of the program.
Scientific program for monitoring in real time or post-processed of ionospheric irregularities and scintillation of GNSS signals
Keywords: Indices fP, FP, IROT, ROTI, σΦ, SΦ and σCHAIN; Ionospheric irregularities; Ionospheric scintillation; ROT